Characteristics of Nonmotor Symptoms in Progressive Supranuclear Palsy. (5th June 2016) - Ou, Ruwei; Song, Wei; Wei, Qianqian; Chen, Ke; Cao, Bei; Hou, Yanbing; Zhao, Bi; Shang, Huifang
Abstract : Objectives . To explore the clinical correlates of nonmotor symptoms (NMS) in progressive supranuclear palsy (PSP) and their differences from healthy controls and patients with Parkinson's disease (PD). Methods . Twenty-seven PSP patients, 27 age- and gender-matched healthy controls (HC), and 27 age- and gender-matched PD patients were included for this case-control study. NMS were assessed using the Nonmotor Symptoms Scale (NMSS, including 9 domains). Results . All PSP patients reported NMS. The frequency and severity of "sleep/fatigue, " "mood/apathy, " "attention/memory, " "gastrointestinal, " "sexual dysfunction, " and "miscellaneous" domains in PSP group were significantly higher than those in HC group (P < 0.05 ). The frequency of "mood/apathy, " "attention/memory, " and "sexual dysfunction" domains and the severity of "attention/memory" and "gastrointestinal" domains in PSP group were significantly higher than those in PD group (P < 0.05 ). The "attention/memory" domain in PSP had a significant but weak-to-moderate correlation with age (R = 0.387, P = 0.046 ) and onset age (R = 0.406, P = 0.036 ). Conclusions . NMS are common in PSP patients. Patients with PSP seem to be subjected to more frequent and severe specific NMS compared to healthy aging subjects and PD patients. Older PSP patients and late-onset patients are likely to be subjected to cognitive decline.